Report
1941-11 038-0024-002 3 NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF AND BASQUE CHILDREN'S TRUST LTD. President. Her Grace The Duchess of Atholl, D.B.E., D.C.L. Chairman. Miss Eleanor F. Rathbone, D.C.L., LL.D., M.P. Vice-Chairman. The Earl of Listowel. Hon. Secretaries. Lady Layton. Mr. Wilfred Roberts, M.P. Mr. D.R. Grenfell, M.P. Hon. Treasurer. Viscount Cecil of Chelwood, P.C., K.C. General Secretary. Mrs. V.E. Miller. Secretary Basque Children's Committee. Miss M. Picken. Welfare Visitor. Dr. M. Camps. Accountant. Mr. S.E. Morris. Auditors. Messrs. John Diamond & Co., Portland House, 73, Basinghall Street, E.C.2. Bankers. Messrs. Coutts & Co., 440, Strand, W.C.1. 39, Victoria Street, S.W.1. Telephone : Abbey 7463 292/946/38/24(II)